The regional law of refugee protection in Africa - Sharpe, Marina, 1979- (Oxford : Oxford University Press, 2018)
The regional law of refugee protection in Africa has never been fully articulated. The extent of the regime was, until recently, narrowly construed as not including human rights law; the history, and some contemporary aspects, of the regional refugee treaties were misunderstood; the nature of the systemic relationship between the regional and international refugee treaties had not been explored nor had discrete relationships between these two refugee instruments and between the regional refugee treaty on the one hand and regional human rights law on the other; and, most importantly, the regional legal regime for refugee protection in Africa had never been treated as a whole in one work. Marina Sharpe fills these gaps by providing the first detailed analytical account of African regional refugee law.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 30, 2018).
Keywords: Refugees -- Legal status, laws, etc. -- Africa; Asylum, Right of -- Africa; Law; International law